Lie group approach to Cauchy's problems : solution of an initial value problem for the Black-Scholes model - Wafo, Soh, Celestin (My University, 1997)
A Lie group assisted method is used to solve explicitly an arbitrary initial value problem for the Black-Scholes equation, This equation plays a crucial role in the mathematics of finance. It was first solved by its inventors for a special initial data. Our solution generalises the well-known Black-Scholes formula.
A research report submitted to the Faculty of Science, University of the Witwatersrand, Johannesburg, in partial fulfilment of the requirements for the degree of Master of Science.
Keywords: Lie groups.; Cauchy problem.; Differential equations, Partial.; Mathematical models.; Business mathematics.